Utilização de projetos de software livre em disciplinas de engenharia de software: a perspectiva do aluno - FERREIRA, Clarice Moraes (2019)
Traditional Software Engineering disciplines commonly prioritize the teaching of methodologies and concepts in small and controlled environments. This decision is partly justified by the difficulty of bringing real software projects into the classroom context. The omnipresence of free software projects, however, contributes to the mitigation of this problem. In particular, several professors already undertake tasks of contribution in free software projects as part of the teaching and evaluation process in their disciplines. However, not so much is known about the students’ perception of having to contribute free software systems in the context of a discipline. This paper aims to clarify the challenges, benefits and perceptions of students. To this end, 14 semi-structured interviews were conducted with students who studied these subjects in five different Brazilian institutions, resulting in several findings not so well known. For example, observing that although teachers indicate the projects for students to work on, students (and also the project community) participate in the process of choosing projects and issues. In addition, we also identified that student contributions varied in terms of both the number of additions and deletions in commits and the use of different programming languages.